ANALISIS KOMPOSISI KIMIA PRODUK PIROLISIS LAMBAT OFF-GRADE RUBBER PADA SUHU 300 °C - Agustina Tri Putri Sitinjak; RR Dirgarini Julia Nurlianti Subagyono; Veliyana Londong Allo; Ari Susandy Sanjaya (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
This study was conducted to determine the yield and chemical composition of slow pyrolysis products of off-grade rubber at 300 °C. From the pyrolysis experiments, the yield of bio-oil was 28.25%. Analysis with Gas Chromatography-Mass Spectrometry showed that the bio-oil from off-grade rubber was mainly composed of γ-Elemene, 1H-Benzocycloheptene, octahydro-3,5,5-trimethyl-9-methylene-, (4aS-cis)-, 1,5-Cycloundecadiene, 8,8-dimethyl-9-methylene-, Geranyllinalool Isomer B, and Geranylgeraniol. Keywords: Slow Pyrolysis, Off-grade Rubber, bio-oil, GC-MS